Transparency in supply chains (TISC): assessing and improving the quality of modern slavery statements - Pinnington, Bruce (Journal of business ethics, 2023)
Transparency lies at the heart of most modern slavery reporting legislation, but while publication of statements is mandatory, conformance with content guidance is voluntary, such that overall, corporate responses have been poor. Existing studies, concentrated in business to consumer rather than inter-organisational contexts, have not undertaken the fine-grained assessments of statements needed to identify which aspects of reporting performance are particularly poor and the underlying reasons that need to be addressed by policy makers. In a novel design, this study utilises the ethical trade initiative assessment framework to evaluate the content of 95 UK government suppliers’ modern slavery statements. The findings suggest that in a modern slavery context, discovery challenges are more important than firms’ attitudes to disclosure. We contribute to the transparency literature through a model contrasting discovery costs and disclosure risks and by identifying the disclosure of unknowns as an additional relevant dimension of disclosure. We then discuss the model in relation to normativity theory to consider options through which the currently low legitimacy of the reporting governance regime can be enhanced and the intended norms established.